Tablica izvoda: Funkcija f (x ) c = const x xα a e x Tablica integrala: (x) Izvod f ′ £ dx = x + c ¤ 0 1 ¥ x n dx = x n +1 +c n +1 αxα −1 ¦ dx = ln x + c x e x dx = e x + c a ln a § x x e x a x dx = ¨ ax +c ln a log a x ln x 1 x ln a 1 x © sin xdx = − cos x + c cos xdx = sin x + c  sin x cos x − sin x  dx cos 2 x dx = tgx + c = −ctgx + c cos x tgx 1 cos x 1 − sin 2 x 1   2 sin 2 x dx ctgx arcsin x x2 + a2 dx  = = 1 x 1 x arctg + c = − arcctg + c1 , a ≠ 0 a a a a 1 x−a ln +c, a ≠ 0 2a x+a arccos x − 1 − x2 1 1− x 1 2 2  x −a dx 2 2 x2 ± a 2 dx a −x 2  = ln x + x 2 ± a 2 + c , a ≠ 0 x x + c = − arccos + c1 , a > 0 a a arctgx arcctgx 1+ x 1 − 1 + x2  2 = arcsin dx x = ln tg +c sin x 2 dx x π = ln tg ( + ) + c cos x 2 4  Površine ravnih figura:   a 2 − x 2 dx = b t2 P= a f ( x) dx , P = ¡ y(t ) ⋅ x t′ (t)dt , P = t1 b 1 ρ 2 (ϕ )dϕ . 2  ¢ β x a2 x a2 − x2 + arcsin + c , a > 0 2 2 a α x 2 + A dx = β x 2 x2 + A + A ln x + x 2 + A + c 2 t2 ! Dužina luka krive: l = a 1 + ( f ′( x)) 2 dx , l = t1 b # ( x t′ (t )) 2 + ( y t′ (t )) 2 dt , l = " ρ 2 (ϕ ) + ( ρ ′(ϕ ))2 dϕ . ρ 3 (ϕ ) sin ϕ dϕ . α t2 $ Zapremina obrtnih tela: V = π f 2 ( x)dx , V = π y 2 (t ) ⋅ xt′ (t)dt , V = a t1 2π 3 β % α Površina omota a obrtnih tela: & ' b t2 ( ) β P = 2π a f ( x ) 1 + ( f ′( x)) dx , P = 2π 2 y (t ) ( x′(t )) 2 + ( y ′(t )) 2 dt , P = 2π ρ (ϕ ) ρ 2 (ϕ ) + ( ρ ′(ϕ )) 2 sin ϕ dϕ . t1 α Maklorenove formule: e x = 1+ sin x = x x2 x n −1 xn θ x + + ... + + R n ( x ) , R n ( x) = e , 0 < θ < 1, x ∈ R . 1! 2 ! (n − 1) ! n! x x3 x5 x 2 n −1 x 2 n +1 − + − ... + (−1) n −1 + R2 n +1 ( x) , R 2 n +1 ( x) = (−1) n cos θ x , 0 < θ < 1, x ∈ R . 1! 3 ! 5! (2 n − 1) ! (2n + 1) ! x2 x4 x 2 n− 2 x 2n + + ... + (−1) n −1 + R2 n ( x) , R 2 n ( x ) = (−1) n cos θ x , 0 < θ < 1, x ∈ R . 2! 4! (2n − 2) ! ( 2n) ! xn x x2 x3 x4 x n −1 , 0 < θ < 1 , − 1 < x ≤ 1 , n > 1. − + − + ... + ( −1) n + R n ( x) , R n ( x) = (−1) n +1 1 2 3 4 ( n − 1) n (1 + θ x) n cos x = 1 − ln(1 + x) = α n α −n (1 + x ) α = ( α ) + ( α ) x + ( α ) x 2 + ... + ( α ) x n −1 + Rn ( x ) , R n ( x) = ( ) x (1 + θ x ) , 0 < θ < 1 , n 0 1 2 n −1 (α ) = k x < 1, α (α − 1)...(α − k + 1) k! n −1 k =0   , α ∈ R , k ∈ N 0 = N ∪ { 0} ; (−1) n x n , 0 < θ < 1, (1 + θ x) n +1 α = 1: 1 = 1+ x (−1) k x k + Rn ( x) R n ( x ) = x < 1. Trigonometrija: sin( x + y ) = sin x cos y + cos x sin y cos( x + y ) = cos x cos y − sin x sin y tg ( x + y ) = tgx + tgy 1 − tgx ⋅ tgy ctgxctgy − 1 ctgx + ctgy ctg ( x + y ) = sin( x − y ) = sin x cos y − cos x sin y cos( x − y ) = cos x cos y + sin x sin y tgx − tgy tg ( x − y ) = 1 + tgx ⋅ tgy ctgxctgy + 1 ctg ( x − y ) = ctgy − ctgx x− y x+ y cos 2 2 x+ y x− y cos x − cos y = −2 sin sin 2 2 sin( x − y ) tgx − tgy = cos x cos y sin x − sin y = 2 sin ctgx − ctgy = sin( y − x) sin x sin y sin x + sin y = 2 sin x+ y x− y cos 2 2 x+ y x− y cos x + cos y = 2 cos cos 2 2 sin( x + y ) tgx + tgy = cos x cos y ctgx + ctgy = sin( x + y ) sin x sin y sin 2 x = 2 sin x cos x cos 2 x = cos 2 x − sin 2 x 2tgx tg 2 x = 1 − tg 2 x ctg 2 x = ctg 2 x − 1 2ctgx 1 [sin( x − y ) + sin( x + y )] 2 1 sin x sin y = [cos( x − y ) − cos( x + y )] 2 1 cos x cos y = [cos( x − y ) + cos( x + y )] 2 sin x cos y = sin 2 x 1 − cos x = 2 2 x 1 + cos x = 2 2 sin x = 2tg x 2 2 cos 2 x 1 + tg 2 x 1 − tg 2 2 cos x = x 1 + tg 2 2 sin 2 x = tg 2 x 1 + tg 2 x cos 2 x = 1 1 + tg 2 x
Sign up to vote on this title
UsefulNot useful